It's one of us (Mira, 2023)
"Olivia Bender designs exquisite home interiors that satisfy the most demanding clients. But her own deepest desire can't be fulfilled by marble counters or the perfect rug. She desperately wants to be a mother. Fertility treatments and IVF keep failing. And just when she feels she's at her lowest point, the police deliver shocking news to Olivia and her husband, Park. DNA results show that the prime suspect in a murder investigation is Park's son. Olivia is relieved, knowing this is a mistake. Despite their desire, the Benders don't have any children. Then comes the confession. Many years ago, Park donated sperm to a clinic. He has no idea how many times it was sold--or how many children he has sired. As the murder investigation goes deeper, more terrible truths come to light. With every revelation, Olivia must face the unthinkable. The man she married has fathered a killer. But can she hold that against him when she keeps such dark secrets of her own?"--

Weapons of opportunity: a novel (Nick Flynn, 3,, 2023)
"When Nick Flynn left the US Air Force to join the Quartet Directorate, he did so with the full knowledge that no one could ever know. This covert private force--called Four by its members--promised him the chance to lead his own missions and make his own decisions. When a former senior CIA executive goes dark, Flynn and his team are ready to step in. What begins as a quiet check on his home turns into a firefight against a familiar enemy who is more dangerous than ever"--